Challenges facing the school performance development system from the viewpoint of educators in Ash Sharqiyah North Governorate, Sultanate of Oman - Alyahmadi, Hamed Hilal Nasser; Almanwari, Said Saif Said (Journal of Educational and Psychological Sciences, 2020)
This study intended to explore the obstacles that are facing school performance development in the Sultanate of Oman in the aspects of system philosophy, school administration, implementation and the human and material resources and the difficulties impeding achieving planned goals from the perspective of administrative supervisors, principals and teachers in the east north governorate. This study utilized descriptive approach. A survey used to collect data and applied upon a sample of 19 administrative supervisors, 22 principles, and 88 teachers from Ash Sharqiyah North Governorate. The results of the study showed that the overall tool has obtained a total average (3.62 out of 5) considered (large) and in aspects level. The administrative factors obtained the highest average (3.68), then executive procedures with an average of (3.68), thirdly, the challenges of material resources with an average of (3.64) and finally the challenges of the philosophy of the school performance system with an average of (3.46) all are significant challenges.The study indicates also that there are some challenges in the implementation process and the financial aspects at the average level. The study recommended principals and development team training about the proper implementation of the school performance tools. The study also recommended that financial support should be provided to schools to implement the system efficiently and in a sufficient way. It also recommended discussing the ultimate report for the performance development system in regular educational meetings.
Keywords: Obstacles; School performance development system; Oman